Criticism Against Material - Oriented Life Reflected In Oscar Wilde`S The Importance Of Being Earnest Drama (1895):A Sociological Approach - Wijayasari, Rini; , Dr. M. Thoyibi, M.S; , Dr. Phil. Dewi Candraningrum, M.Ed (2015)
The major problem of this study is how criticism against material - oriented life reflected in The Importance of being Earnest drama by Oscar Wilde on 1895. The objective of this study is to analyze the drama based on the sociological analysis. In analyzing The Importance of being Earnest drama, the writer uses qualitative method and Sociological approach. The data sources consist of primary data and secondary data sources. The primary data source is The Importance of being Earnest drama and the secondary data sources are books or any information related to material - oriented life. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusions. First, based on the social historical background of the English society at the end of the 19th century, it shows that Oscar Wilde wants to express his idea about difference habit and lifestyle between upper and lower classes. Second, based on material - oriented life, the conclusion is that there is material - oriented life in The Importance of being Earnest drama. Oscar Wilde shows that nature of material - oriented life cannot be separated from the material, so the people justify any means to get what they want. Such as lies and hypocrisy to get their love as portrayed in the drama. Third, based on the play related to the English society at the end of the 19th century, Oscar Wilde shown the issues raised in this works are about marriage and social norms, which are social class distinctions made the Victorian society at that time weak so they justify a variety of ways to get what they want included in the wedding. Social class differences make the separation between the rich and the poor